The Promise of Chimeric Antigen Receptor Engineered T Cells in the Treatment of Hematologic Malignancies. Issue 1 (January 2016) - Nagle, Sarah J.; Garfall, Alfred L.; Stadtmauer, Edward A.
Abstract : Abstract: Relapsed and refractory hematologic malignancies have a very poor prognosis. Chimeric antigen receptor T cells are emerging as a powerful therapy in this setting. Early clinical trials of genetically modified T cells for the treatment of non-Hodgkin lymphoma, chronic lymphocytic leukemia, and acute lymphoblastic leukemia have shown high complete response rates in patients with few therapeutic options. Exploration is ongoing for other hematologic malignancies including multiple myeloma, acute myeloid leukemia, and Hodgkin lymphoma (HL). At the same time, the design and production of chimeric antigen receptor T cells are being advanced so that this therapy can be more widely utilized. Cytokine release syndrome and neurotoxicity are common, but they are treatable and fully reversible. This review will review available data as well as future developments and challenges in the field.